2020
DOI: 10.3390/biom10091337
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine IL-1β and Piperine Complex Surveyed by Experimental and Computational Molecular Biophysics

Abstract: The bioactive piperine, a compound found in some pepper species, has been widely studied because of its therapeutic properties that include the inhibition of an important inflammation pathway triggered by interleukin-1 beta (IL-1β). However, investigation into the molecular interactions between IL-1β and piperine is not reported in the literature. Here, we present for the first time the characterisation of the complex formed by IL-1β and piperine through experimental and computational molecular biophysical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Molecular docking studies have shown direct binding of piperine to PTGS2 with a score of 5042 kcal/mol [ 71 ]. However, piperine also has a high binding affinity for IL-1β, which has a binding site for piperine with an affinity constant of 14.3 × 104 M −1a 298 K, and spontaneous interaction between these molecules has been observed (∆G = −25 kJ/mol) [ 72 ]. This evidence, together with the results of our study, supports the hypothesis that piperine may have bound to these mediators, preventing the binding of IL-1β to its receptor and the synthesis of PGE2, and resulting in an anti-inflammatory and antitumor effect in the tumor cells ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking studies have shown direct binding of piperine to PTGS2 with a score of 5042 kcal/mol [ 71 ]. However, piperine also has a high binding affinity for IL-1β, which has a binding site for piperine with an affinity constant of 14.3 × 104 M −1a 298 K, and spontaneous interaction between these molecules has been observed (∆G = −25 kJ/mol) [ 72 ]. This evidence, together with the results of our study, supports the hypothesis that piperine may have bound to these mediators, preventing the binding of IL-1β to its receptor and the synthesis of PGE2, and resulting in an anti-inflammatory and antitumor effect in the tumor cells ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both methods (the binding equilibrium and Hill methods) differed somewhat in terms of the absolute value of the binding constant. This difference found is due to the fact that the binding equilibrium method uses a first order chemical reaction model while the Hill method does not, as discussed previously in the literature [ 16 , 31 , 40 ].…”
Section: Resultsmentioning
confidence: 91%
“…Related to the thermochemistry of complexation, the process occurred with the absorption of heat (ΔH > 0), being an endothermic process. In addition, both terms T.ΔS and ΔH are positive values that reveal the non-specific interactions as the main interactions that drove the complexation [ 20 , 22 , 23 ]. This information is further reinforced in the molecular modelling section, which points to a single hydrogen bond formed in the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure of piperine ( Figure 1 ) is composed of two groups, electronically conjugated-benzodioxole and pentadienone chromophore [ 19 ]. This structural feature leads to characteristic ultraviolet (UV) absorptions [ 20 ]. A review reported in the literature this year (2022) gathered a set of studies of important targets that interact (experimental and computational results) with piperine [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation